STUDI DESKRIPTIF DESTINATION IMAGE KOTA MALANG MENURUT PERSPEKTIF WISATAWAN SURABAYA - Christy Jusuf Kurniawan (CALYPTRA, 2015)
The purpose of this research is to identify the destination image of Malang City according the avluation from tourists from Surabaya. The research avriable is destination image. The number of samples are 300 samples. Data analysis technique are: descriptive analysis, devaition standard, bar chart, and cross tabulation. The result of this reasearch showing that tourists from Surabaya have evaluate the destination image of Malang City is moderately high. The evaluation from four of destination image attributtes include: attributes-functional characteristic, functional characteristic-holistic, holistic psychological characteristic, and attributes-psychological characteristic.